PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA PEMBELAJARAN PENDIDIKAN JASMANI SISWA KELAS XI SMA NEGERI 1 MAJENE - Ilham Kamaruddin; La Kamadi; Yasriuddin Yasriuddin; Ahmad Assagaf Rahmat (STKIP PGRI Situbondo, 2022)
This study aims to analyze the learning outcomes of basic passing techniques using the inner foot using the Student Teams Achievement Division (STAD) cooperative model in class XI students of SMA Negeri 1 Majene. This study uses descriptive research with quantitative and qualitative approaches involving one variable, namely the learning outcomes of inner foot passing. The population of this research is the students of class XI MIA 4 SMA Negeri 1 Majene with a sample of 38 students obtained by purposive sampling. The data collection technique uses the learning outcomes of inner foot passing. The results of the study found that the learning outcomes of inner foot passing were seen from 3 aspects, namely affective with a value of 97.4% (37 students), cognitive with a value of 94.7% (36 students) and psychomotor with a value of 94.7% (36 students). These three aspects have met the KKM. However, there are still students who have not met the KKM, namely from the affective aspect of 1 student (2.6%), cognitive aspect of 2 students (5.3%), and psychomotor aspect of 2 students (5.3%). It can be concluded that by using the cooperative learning model Student Teams Achievement Division (STAD) can classically complete the learning outcomes of inner foot passing in the soccer game in class XI MIA 4 SMA Negeri 1 Majene both in terms of affective, cognitive and psychomotor aspects